2013
DOI: 10.1088/0963-0252/22/3/035008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on the optimization of pulse-modulated radio-frequency discharges

Abstract: In this paper we present an experimental and computational study on the optimization of pulse-modulated radio-frequency (rf) discharges at atmospheric pressure. Based on the measured and simulated data, to improve the electron density and electron temperature in a pulse-modulated rf discharge, a lower modulation frequency, smaller than 50 kHz, with a higher duty cycle, usually larger than 30%, should be used. But to reduce the power consumption and lower the gas heating, the duty cycle should be smaller than 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
4
33
0
2
Order By: Relevance
“…Moreover, the previous experimental and computational investigation have shown that when the duty cycle is small than 60% the gas heating effects can be effectively eliminated. [1,12] According to the present computational data and the investigation in refs., [14,15] the production of ground state atomic oxygen is mainly through…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Moreover, the previous experimental and computational investigation have shown that when the duty cycle is small than 60% the gas heating effects can be effectively eliminated. [1,12] According to the present computational data and the investigation in refs., [14,15] the production of ground state atomic oxygen is mainly through…”
Section: Resultssupporting
confidence: 57%
“…In a pure helium, RF plasma under pulse modulation, the experimental and computational results have indicated that the current density always increases with the duty cycle (with different increasing rates), and the maximum current density under pulse modulation is impossible to be larger than the amplitude of current density in a continuous RF discharge. [12] Figure 1 presents the RMS current density versus the duty cycle for various modulation frequencies at a given oxygen admixture of 0.6%. In a continuous RF discharge, the amplitude of current density under the given discharge conditions is a constant value of about 42.68 mA cm À2 , indicated as a black dash line in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations